2014
DOI: 10.1155/2014/860658
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion Tensor Imaging Studies on Chinese Patients with Social Anxiety Disorder

Abstract: The aim of this study was to explore white-matter disruption in social anxiety disorder (SAD) patients by using diffusion tensor imaging (DTI) and to investigate the relationship between cerebral abnormalities and the severity of the symptoms. Eighteen SAD patients and age- and gender-matched healthy controls were recruited. DTI scans were performed to measure fractional anisotropy (FA) and apparent diffusion coefficient (ADC) for each subject. We used voxel-based analysis to determine the differences of FA an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 40 publications
1
14
0
Order By: Relevance
“…However, one study reported globally reduced fractional anisotropy (FA, Baur et al, 2013a). Significant FA changes were detected in the left uncinate fasciculus in three studies (Baur et al, 2013a;Baur et al, 2011, Qiu et al, 2014, with one study finding no difference in the left, but reduced FA in the right uncinate fasciculus (Phan et al, 2009). In the superior fasciculus, apparent diffusion coefficient (ADC) was reduced bilaterally in one study, which also reported reduced FA on the left side (Qiu et al, 2014), which is paralleled by another study (Baur et al, 2011).…”
Section: Structural-anatomical Changes In Sad (Table 6)mentioning
confidence: 88%
See 3 more Smart Citations
“…However, one study reported globally reduced fractional anisotropy (FA, Baur et al, 2013a). Significant FA changes were detected in the left uncinate fasciculus in three studies (Baur et al, 2013a;Baur et al, 2011, Qiu et al, 2014, with one study finding no difference in the left, but reduced FA in the right uncinate fasciculus (Phan et al, 2009). In the superior fasciculus, apparent diffusion coefficient (ADC) was reduced bilaterally in one study, which also reported reduced FA on the left side (Qiu et al, 2014), which is paralleled by another study (Baur et al, 2011).…”
Section: Structural-anatomical Changes In Sad (Table 6)mentioning
confidence: 88%
“…In the superior fasciculus, apparent diffusion coefficient (ADC) was reduced bilaterally in one study, which also reported reduced FA on the left side (Qiu et al, 2014), which is paralleled by another study (Baur et al, 2011). However, two studies found no difference in at least one side of the superior fasciculus (Baur et al, 2011 No changes in FA were reported for the inferior frontooccipital fasciculus in two studies (Baur et al, 2013a;Phan et al, 2009), while one study showed reduced ADC (Qiu et al, 2014). There is no evidence for increased FA in white matter in most of the existing studies (Phan et al, 2009, Baur et al, 2013a, Qiu et al, 2014) except for increased FA and fibre density in one study .…”
Section: Structural-anatomical Changes In Sad (Table 6)mentioning
confidence: 98%
See 2 more Smart Citations
“… 23 , 24 , 25 Patients with social anxiety disorder were reported to exhibit anomalies in WM and deficits in the left insula and the left inferior frontal gyrus were associated with the severity of social anxiety. 26 At the subclinical level, individual differences in trait anxiety were also associated with WM connectivity in the left temporal cortex and the uncinate fasciculus. 27 , 28 , 29 Specific impairments were observed in the corpus callosum and the uncinate fasciculus in adolescence-onset patients.…”
Section: Introductionmentioning
confidence: 98%